Uji Kesukaan Hasil Jadi Kue Brownies Menggunakan Tepung Terigu dan Tepung Gandum Utuh - Wahyuningtias, Dianka; Putranto, Trias Septyoari; Kusdiana, Raden Nana (Binus Business Review, 2014)
The purpose of this research is to discover the degree of preferences in flavor, aroma, color, shape, and texture in the Brownies using 100% whole grain flour and to discover the public acceptability to the Brownies using 100% whole wheat flour. The research is using Experimental Research. The research is using a descriptive statistical analysis method that is used to analyze data in ways that describe or depict the data that has been collected. The results showed that the average yield of the Brownies using 100% whole grain flour is higher than Brownies with wheat flour. On the basis of these results, it can be concluded that people prefer like Brownies using whole grain flour instead of Brownies using wheat flour.